2020
DOI: 10.3389/fcell.2020.586628
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Nano-Morphology of the Prolamellar Body in Etiolated Arabidopsis thaliana Plants With Disturbed Pigment and Polyprenol Composition

Abstract: Bykowski et al. Diverse Nano-Morphology of Prolamellar Bodies to wild type plants. The decrease in the relative content of β-branch xanthophylls in aba1-6 plants was manifested by local disturbances in the paracrystalline structure of the PLB network. Therefore, proper levels of particular etioplast pigments are essential for the formation of stable and regular PLB structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 89 publications
1
16
0
Order By: Relevance
“…Gaussian deconvolution and further spectral and biochemical analyses of isolated and fractionated etioplast inner membranes revealed the presence of other minor Pchlide forms, like for instance smaller oligomers (probably dimers) of Pchlide:LPOR:NADPH ternary complexes with emission maximum at 644 nm which are also photoactive and are suggested to be located to the edge of the PLB membranes (Böddi et al, 1990 , 1991 , 1992 ). In addition, a non-photoactive Pchlide molecular subpopulation hypothetically located to the central regions of PLBs and having fluorescence emission maximum at around 670 nm was also described ( Figure 3 ) (Böddi et al, 1990 ; Bykowski et al, 2020 ). Upon short (already μs-long) illumination the fluorescence emission of Pchlide:LPOR:NADPH oligomers with emission maxima at 655 nm disappears, and that of the freshly produced Chlide:LPOR:NADP + oligomers appears at 690 nm ( Figure 3 ) (Böddi et al, 1990 ).…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Gaussian deconvolution and further spectral and biochemical analyses of isolated and fractionated etioplast inner membranes revealed the presence of other minor Pchlide forms, like for instance smaller oligomers (probably dimers) of Pchlide:LPOR:NADPH ternary complexes with emission maximum at 644 nm which are also photoactive and are suggested to be located to the edge of the PLB membranes (Böddi et al, 1990 , 1991 , 1992 ). In addition, a non-photoactive Pchlide molecular subpopulation hypothetically located to the central regions of PLBs and having fluorescence emission maximum at around 670 nm was also described ( Figure 3 ) (Böddi et al, 1990 ; Bykowski et al, 2020 ). Upon short (already μs-long) illumination the fluorescence emission of Pchlide:LPOR:NADPH oligomers with emission maxima at 655 nm disappears, and that of the freshly produced Chlide:LPOR:NADP + oligomers appears at 690 nm ( Figure 3 ) (Böddi et al, 1990 ).…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 96%
“…Data indicate the role of carotenoids [zeaxanthin and violaxanthin (Ouazzani Chahdi et al, 1998 ); neoxanthin and violaxanthin (Bykowski et al, 2020 ); the accumulation of poly-cis xanthophylls (Park et al, 2002 ; Cuttriss et al, 2007 )] and lipids [MGDG (Aronsson et al, 2008 ; Fujii et al, 2017 ); and MGDG, PG, and SQDG (Gabruk et al, 2017 ; Nguyen et al, 2021 )] in the formation of the photoactive enzyme complexes and the PLBs. Similarly, carotenoids (Denev et al, 2005 ) were suggested to be involved in the membrane association of LPOR.…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an experiment does not require any special sample preparation-PLBs can in principle be investigated in in vivo conditions, directly in ethiolated leaves, thus yielding more precise average unit cell values and space group assignment. Ultimately, PLB ultrastructures from various plants and photosynthetic mutants can be investigated and compared, as in Bykowski et al (2020), and a continuous light-induced PLB disassembly can be ideally followed as well.…”
Section: Prolamellar Bodiesmentioning
confidence: 99%
“…The PLB is considered as a lipid reservoir during tubular-lamellar transition increasing the efficiency of grana formation (Armarego-Marriott et al, 2019;Pipitone et al, 2021). The number of PLB building blocks play a crucial role in maintaining its structure, including protochlorophyllide:light-dependent protochlorophyllide oxidoreductase:NADPH complex as well as particular galactolipids and carotenoids (Floris and Kühlbrandt, 2021;Bykowski et al, 2020;Cazzonelli et al, 2020;Franck et al, 2000;Fujii et al, 2019;Nguyen et al, 2021;Sperling et al, 1998). Although the role of light-dependent protochlorophyllide oxidoreductase in membrane tubulation was proven recently using electron cryo-tomography techniques (Nguyen et al, 2021;Floris and Kühlbrandt, 2021), factors governing the transition of tubular arrangements into cubic configuration remain elusive (Wietrzynski and Engel, 2021).…”
Section: Almsherqi Et Al 2012)mentioning
confidence: 99%